Realiza las siguientes operaciones : a) \( 3 \cdot\left(2 x^{2}-4 x+5\right)-\left(6 x^{2}-12 x+15\right)= \) b) \( 2 \cdot\left(2 x^{3}-3 x+4\right)-3 \cdot\left(x^{3}-2 x^{2}+x-1\right)= \) c) \( 4 \cdot\left(x^{3}-2 x\right)-2 \cdot\left(x-x^{3}\right)= \) d) \( -2 \cdot(-3 x+4)-(5 x+8)= \) e) \( x-8-5 x-8= \) f) \( -(9 x-4)+5 \cdot(3 x-2)= \) g) \( 5 x+3 y-2 \cdot(x+6 y)+3 \cdot(2 x-8)= \) h) \( -(8 x-5 x+4)-4 \cdot(4 x-1)= \) i) \( 5 \cdot\left(x^{2}-3 x+1\right)-\left(2 x^{2}+5 x+3\right)= \) j) \( -\left(x^{2}-3 x\right)+x^{3}-2 x^{2}+x-4 \cdot\left(x^{2}-5 x\right)= \) k) \( \left(4 x^{2}-2 x+1\right) \cdot\left(x^{2}-2\right)= \) l) \( \left(-3 x^{3}+6 x^{2}-x-4\right) \cdot\left(3 x^{2}-5 x\right)= \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
a) \( 3 \cdot\left(2 x^{2}-4 x+5\right)-\left(6 x^{2}-12 x+15\right) = 0 \) b) \( 2 \cdot\left(2 x^{3}-3 x+4\right)-3 \cdot\left(x^{3}-2 x^{2}+x-1\right) = x^{3}+3 x+10 \) c) \( 4 \cdot\left(x^{3}-2 x\right)-2 \cdot\left(x-x^{3}\right) = 6 x^{3}-10 x \) d) \( -2 \cdot(-3 x+4)-(5 x+8) = x-16 \) e) \( x-8-5 x-8 = -4 x-16 \) f) \( -(9 x-4)+5 \cdot(3 x-2) = 6 x-6 \) g) \( 5 x+3 y-2 \cdot(x+6 y)+3 \cdot(2 x-8) = -x - 9y - 24 \) h) \( -(8 x-5 x+4)-4 \cdot(4 x-1) = -12 x - 8 \) i) \( 5 \cdot\left(x^{2}-3 x+1\right)-\left(2 x^{2}+5 x+3\right) = 3 x^{2}-20 x+2 \) j) \( -\left(x^{2}-3 x\right)+x^{3}-2 x^{2}+x-4 \cdot\left(x^{2}-5 x\right) = -2 x^{2} + x^{3} + 19 x - 4 \) k) \( \left(4 x^{2}-2 x+1\right) \cdot\left(x^{2}-2\right) = 4 x^{4}-8 x^{2}-2 x^{3}+4 x+1 \) l) \( \left(-3 x^{3}+6 x^{2}-x-4\right) \cdot\left(3 x^{2}-5 x\right) = -9 x^{5}+15 x^{4}+18 x^{4}-30 x^{3}+3 x^{2}+20 x \)